Recommendations for the treatment of axial spondyloarthritis: An analysis of the updated ASAS/EULAR 2022 clinical guidelines - Sh. F. Erdes; T. V. Dubinina (Научно-практическая ревматология, 2025)
The article discusses the 2022 updated version of the collaborative ASAS/EULAR (Assessment in SpondyloArthritis international Society/European Alliance of Associations for Rheumatology) recommendations for the treatment of axial spondyloarthritis.